The Risk of Absenteeism among Workers with Psoriasis - Rakhmi Savitri Hoesein; Indah S. Widyahening; Dewi S. Soemarko (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: Psoriasis is a chronic, painful, destructive, and disabling disease that has no cure, with a large negative impact on a patient’s quality of life. Sick leave is one of common challenges for people with psoriasis.Aim: To know the absenteeism risk of workers with psoriasis.Method: A literature search using search engine PubMed and Google Scholar was conducted. The inclusion criteria are systematic review, cohort, or case control studies; the subjects of studies are workers; the indicator listed in the title is psoriasis that is not differentiated in any form or type of psoriasis; and the outcome is absenteeism and its synonyms. The exclusion criteria are the articles not written in English, full text is not available, the articles have been used in the recent systematic review, the subjects are blue collar worker or non-office worker, and not relevant according to PICO. Critical appraisal was conducted using standard validity criteria for etiologic/harm/risk studies.Result: A retrospective matched case control analysis was selected with the level of evidence 3b –. Psoriasis patients were significantly more likely than controls to skip working hours (OR = 1.37; 95% CI 1.00 - 1.89; p <0.05) and days (OR = 1.21; 95% CI 0.72 - 2.05) at the previous week due to health reasons. Conclusion: Psoriasis increases the risk of sick leave/absenteeism due to illness than those without psoriasis.